The Used of Padlet In Teaching Performing Arts During the COVID-19 Pandemic - Vimala Murti Pitra Tunggal Jaya; Maria Goretti Octavia Pepe; Brigitta Wastu Warsiki (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
The COVID-19 pandemic has caused worldwide disruption and affects every aspect of human life, including education. Before this situation, the proper application of technology has been an important tool to support the learning process through the online learning approach. This study aims to identify the use of padlet in teaching performing arts during the COVID-19 pandemic. The research used a qualitative method using literature review and action research. The subject of this research is the Performing Arts teachers. Self-administered interviews were conducted with other Performing Arts teachers as an observation material in this research study. The majority of the Performing Arts teachers agreed that padlet is one of the easy-to-use applications that is beneficial during online learning. The researcher also conducted research design in the form of a self-administered questionnaire. This study involved sixty-four (64) students from grades four and five in extending the understanding of the use of padlet from students’ views. From the questionnaire, 31 (49.2%) strongly agree with the idea that padlet is useful for online learning, 22 (34.9%) agree, 9 (14.3%) neutral, and 1 (1.6%) strongly disagree. Hence, the result emphasized that the padlet is useful for both teachers and students, especially during the home learning program in the COVID-19 pandemic